The Democratic Challenge of Incorporation: International Human Rights Treaties and National Constitutions - Harrington, Joanna (Victoria University of Wellington Law Review, 2007)
According to Canadian Supreme Court Justice Claire L’HeureuxDubé, the global judicial community is engaged in a process of dialogue, especially in cases involving the determination of constitutionally protected human rights. However, as this author notes, if there is a process of dialogue taking place, it does not always include the international treaty monitoring bodies supported by the United Nations, even when there is a treaty link between the international body and the domestic state. The author considers the approach taken by courts in South Africa, the United Kingdom and Ireland with respect to the judicial consideration of international human rights decisions, linking the prospects for dialogue to the express mandates to consider such case law within their constitutions, while contrasting the experience with that of Canada and New Zealand, where no such express imperative exists. The author concludes by suggesting that such a constitutionallydetermined approach may well be the most democratic means of reconciling a state’s international commitments with its domestic law.